Perception about human papillomavirus vaccination among middle adolescent school girls in Addis Ababa, Ethiopia 2023: qualitative study - Abel Wubu; Bargude Balta; Amsale Cherie; Ketema Bizuwork (BMC, 2023)
Abstract Background Human papillomavirus vaccine uptake among school girls in Ethiopia was still low and uptake was majorly related to perception regarding the vaccine. This study explored school girls' perceptions of Human papillomavirus vaccination in Addis Ababa, Ethiopia. Objectives The main aim of this study was to explore the perception of secondary school girls towards Human Papilloma Virus vaccine in Addis Ababa, Ethiopia 2023. Methods A qualitative research using focused group discussions were used to explore middle adolescent school girls' perceptions of Human papillomavirus in Addis Ababa Ethiopia from March 2023-April 2023. A focus group discussion guide was employed with potential probes to achieve study objectives. A convenience sampling technique was performed to select study participants. The collected data were transcribed and translated into English and thematic analysis was done by using Atlas-Ti software version 7.5.16. Result Two dominant themes emerged from the study; perceived benefits and potential barriers to Human papillomavirus vaccine uptake. Poor awareness, lack of family support, perception of poor vaccine quality, fear of side effects, misconceptions, and myths are potential barriers to the Human papillomavirus vaccine. Some students perceive the vaccine as important in the prevention of cervical cancer, others are not sure about the importance of the vaccine and many students think that the vaccine can cause infertility and other beliefs it can cause diseases. Conclusion The perceived benefits of the Human papillomavirus vaccine was; it prevents cervical cancer enhance acceptability and can be an important motivation for Human papillomavirus vaccination among students. The main barriers to vaccine uptake and acceptance were; lack of awareness, misconceptions, and myths, lack of credible information sources of vaccines, perception of poor vaccine quality, Poor family support, and cultural and religious perspectives. We recommend the development of strong collaborations that work on identified challenges.